(untitled) (Journal of Computational Mathematics, 2018)
The Chebyshev polynomials have good approximation properties which are not affected by boundary values. They have higher resolution near the boundary than in the interior and are suitable for problems in which the solution changes rapidly near the boundary. Also, they can be calculated by FFT. Thus they are used mostly for initial-boundary value problems for P.D.E.'s (see [1, 3-4, 6, 8-11]). Maday and Quarterom discussed the convergence of Legendre and Chebyshev spectral approximations to the steady Burgers equation. In this paper we consider Burgers-like equations. cases ∂_iu+F(u)_x-vu_zx=0, & -1≤x≤1, 0＜t≤T u (-1,t) =u (1,t) =0, & 0≤t≤T & (0.1) u (x,0) =u_0(x), & -1≤x≤1 cases where FC(R) and there exists a positive function AC(R) and a constant p＞1 such that |F(z+y)-F(z)|≤ A(z)(|y|+|y|^p). We develop a Chebyshev spectral scheme and a pseudospectral scheme for solving (0.1) and establish their generalized stability and convergence.